The Utilization of Computer-Based Interactive Multimedia in Improving Entrepreneurial Attitudes of High School Students - Rejekiningsih, Triana; Sudiyanto, Sudiyanto; Budiarto, Mochamad Kamil (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Entrepreneurship education is important to be delivered by students in the digital era. Through an entrepreneurial learning process that is integrated with the use of digital learning media, it is hoped that it will create a more dynamic, active and student-centered learning environment so that it can facilitate students in achieving the learning goals that have been set. This study aims to convey the results of the interactive multimedia effectiveness test on improving students' entrepreneurial attitudes in learning craft and entrepreneurship for high school students. This research method is an experimental method with a quasi-experimental design with pre and posttest in the control class and experimental class. The data collection instrument used was an attitude scale questionnaire. This study was followed by high school students, the sample selection used cluster random sampling which was taken in a certain class which is equivalent. The results showed that through the use of interactive multimedia, there was a significant effect and was followed by an increase in students' entrepreneurial attitudes. This study concludes that interactive multimedia is considered quite effective in influencing and improving students' entrepreneurial attitudes as an effort to achieve learning objectives. Therefore, interactive multimedia is very suitable for use as a learning medium for craft and entrepreneurship subjects in high school.